2010
DOI: 10.1016/j.bbabio.2010.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Absence of mitochondrial uncoupling protein 1 affects apoptosis in thymocytes, thymocyte/T-cell profile and peripheral T-cell number

Abstract: Our laboratory has previously demonstrated the presence of constitutively expressed mitochondrial uncoupling protein 1 in mouse thymocytes. In our endeavours to understand the role of mitochondrial uncoupling protein 1 in thymocyte function, we compared cell profiles in thymus and spleen of wild-type with those of UCP 1 knock-out mice, which in turn led to comparative investigations of apoptotic potential in thymocytes from these mice. We demonstrate that spleen cell numbers were reduced approximately 3-fold i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Interestingly, WAT can exert nonshivering thermogenesis with a UCP1-independent pathway (155,156). UCP1 has also been found in thymocytes and demonstrated to be involved in the maturation and fate determination of developing T-cells (157-159). Sale et al (160) found that UCP1 is expressed in islets and associates with the acute insulin response to glucose.…”
Section: Mitochondrial Proton Leakmentioning
confidence: 99%
“…Interestingly, WAT can exert nonshivering thermogenesis with a UCP1-independent pathway (155,156). UCP1 has also been found in thymocytes and demonstrated to be involved in the maturation and fate determination of developing T-cells (157-159). Sale et al (160) found that UCP1 is expressed in islets and associates with the acute insulin response to glucose.…”
Section: Mitochondrial Proton Leakmentioning
confidence: 99%
“…The reader can refer to excellent reviews on these subjects in ( 72 , 185 , 217 ). Also beyond the scope of this review are the role of constitutively expressed UCP1 in thymocytes as a factor in determining T cell population selection ( 4 , 76 ) and mitochondrial UCPs in plants ( 410 ) and unicellular eukaryotes ( 432 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, Ucp1 expression was increased in 12-mo-old recuperated thymi. Given that a murine thymic Ucp1 knockout model demonstrated decreased T-cell apoptosis (42), that increase may confer a potential for increased T-cell apoptosis in old recuperated rats.…”
mentioning
confidence: 99%